The Effect of Synthetic and Commercial Nano-Magnetite on the Electromagnetic Absorbance Behavior of Magnetic Wood - Rahayu, Istie Sekartining; Sabarna, Aqila Alya Nabila; Wahyuningtyas, Irma; Ismail, Rohmat; Prihatini, Esti; Darmawan, Wayan; Laksono, Gilang Dwi; Alipraja, Irsan (Jurnal Sylva Lestari, 2024)
Magnetic wood with good electromagnetic wave absorption properties was prepared by comparing synthetic and commercial nano-magnetite (Fe3O4-NP) as sengon (Falcataria moluccana) wood impregnation solution. The co-precipitation method produced a synthetic nano-magnetite with NH4OH as a weak base precursor. Meanwhile, the commercial one was purchased from a supplier. Three levels of nano-magnetite concentration (1%, 2.5%, and 5%) were dispersed in deionized water. The impregnation process was done by applying a vacuum of 0.5 bar for 120 minutes, followed by a pressure of 1 bar for 120 minutes. The results showed that the commercial nano-magnetite caused more improvements in weight percent gain, density, and hardness than the synthetic nano-magnetic, although they were insignificantly different. There was also a reduction in brightness with the overall color change being categorized into other colors because the color became darker with increasing nano-magnetite concentration in both woods. The absorbance capacity of the synthetic nano-magnetite-treated wood was larger than the commercial nano-magnetite-treated wood. This synthetic nano-magnetite-treated wood had been optimally treated at a 5% concentration, making it suitable for use as electromagnetic wave shielding material because it can absorb almost 100% electromagnetic waves. Keywords: Fe3O4, impregnation, nano-magnetite, sengon wood, shielding materials